(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The paper presents attempts to main focus on the governmentalfactors of Kengal Hanumanthaiah’s. The paper places of interest theparticipation of Kengal Hanumanthaiah in the independence association and hisrole in the fusion of Karnataka. The paper represents Kengal Hanumanthaiah’srole in Politics, the administrative dream of Kengal Hanumanthaiah and how thetemporal and spatial dimensions got interlinked with politics during hisperiod. The main objective of this paper is to discuss the political and socialvision of Kengal Hanumanthaiah inKarnataka.